Can women empowerment boost dietary diversity among children aged 6–23 months in sub-Saharan Africa? - Richard Gyan Aboagye; Irene Esi Donkoh; Joshua Okyere; Abdul-Aziz Seidu; Bright Opoku Ahinkorah; Sanni Yaya (Tropical Medicine and Health, 2024)
Abstract Background The empowerment of women has implications on the health and dietary needs of children. Using the survey-based women’s empowerment index (SWPER), we examined the association between women’s empowerment and dietary diversity among children aged 6–23 months in sub-Saharan Africa. Methods Data from the Demographic and Health Surveys of 21 countries were utilized. Descriptive spatial map was used to present the proportions of dietary diversity among the children. Multilevel binary logistic regression was used to examine the association between SWPER and dietary diversity. Results Overall, 22.35% of children aged 6–23 months had adequate minimum dietary diversity (MDD) in sub-Saharan Africa. The countries with the highest proportions of adequate MDD were Angola, Benin, Madagascar, Rwanda, Sierra Leone, and South Africa. South Africa had the highest proportion of MDD (61.00%), while Liberia reported the least (9.12%). Children born to mothers who had high social independence were more likely to have adequate MDD compared to those with low social independence [aOR = 1.31, 95% CI 1.21, 1.41]. In addition, children born to women with medium [aOR = 1.12; 95% CI 1.03, 1.21] and high decision-making [aOR = 1.25, 95% CI 1.14, 1.37] were more likely to receive MDD than those with low decision-making. Conclusions Insufficient dietary diversity is evident among children aged 6–23 months in sub-Saharan Africa. MDD in children is influenced by women's empowerment. Policies and interventions promoting women's empowerment can enhance MDD, especially for vulnerable groups in rural and poorer households. It is crucial to leverage media and poverty reduction strategies to improve MDD among children in sub-Saharan African countries.